Detour phase computer generated holograms of weakly scattering surfaces - Escoto, Esmerando R. (Institute of Physics, College of Science, University of the Philippines Diliman, 2016)
We have designed computer generated holograms for the reconstruction of light coming from weakly scattering surfaces, by modifying the detour phase hologram technique in order to accommodate a partially developed speckle field. A thorough discussion on hologram generation techniques is presented to highlight the advantage of using the detour phase hologram technique or the said purpose. The computed holograms are planned as an alternativ to weakly scattering diffusers, which on previous works are especially fabricated via photolithography or encoded in a spatial light modulator, for the purpose of single-beam multiple-intensity reconstruction (SBMIR) technique. The holograms were shown to be able to reconstruct a speckle field with variable depth of randomization, and the retrieval of the phase of an object is experimentally demonstrated using the the holograms in the SBMIR technique.